Juridical Analysis of the Postponement of Execution of Inherited Land Due to Error in Objecto in Supreme Court Decision Number 204 K/Pdt/2019: English - Debby Parhusip, Ewis; Yamin, Muhammad; Mulhadi (CV. ARGA FARMA, 2024)
This study examines the juridical and non-juridical obstacles to the execution of court decisions in land inheritance disputes, focusing on error in objecto as highlighted in Supreme Court Decision Number 204 K/Pdt/2019. The case involved a geographical misidentification of the disputed object, which significantly delayed the execution process and hindered the enforcement of the court's ruling. Employing a normative juridical approach, this research utilizes statutory, case, and document analysis to explore the underlying issues. The findings reveal that the primary factors obstructing execution include error in objecto, objections from the judgment debtor, incompetence among law enforcement officers, lack of coordination and support from local government authorities, and the financial burden associated with the execution process. These challenges not only undermine the principle of legal certainty but also perpetuate substantive injustice for litigants. To address these issues, the study proposes preventive measures such as optimizing local inspections (descente), leveraging geospatial technology, and enforcing stricter standards against ambiguous lawsuits (obscuur libel). Corrective measures include the use of judicial review, Supreme Court advisory opinions, and sanctions for negligent judicial officers. By implementing these recommendations, the judiciary can enhance the effectiveness and enforceability of its decisions, ensuring greater legal certainty and fairness in land dispute resolutions.